Historical watershed stressors for the Laurentian Great Lakes. (29th October 2018) - Reavie, Euan D.; Cai, Meijun; Brown, Terry N.
Abstract: This report provides a detailed set of historical stressor data for 60 watersheds comprising the Laurentian Great Lakes basin. Archival records were transcribed from public records to create quantitative data on human activities: population, mining, deforestation, and agriculture. Yearly records of stressors are provided from 1780 through 2010. These data may be used to track historical impacts on Great Lakes coastal and open water conditions. They may further be used to examine corresponding effects on response variables such as biological communities quantified during monitoring and palaeoecological programmes. Open Practices: This article has earned an Open Data badge for making publicly available the digitally‐shareable data necessary to reproduce the reported results. The data is available athttps://doi.org/10.1594/PANGAEA.885879 . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .